OPTIMASI FREKUENSI PEMBERIAN VITAMIN C PAD A PAKAN KOMERSIAL UNTUK PENGENDALIAN PENYAKIT KOI HERPES VIRUS (KHV) PADA IKAN MAS (Cyprinus carpio Linn.) - Taukhid Taukhid; Angela Mariana Lusiastuti; Kusumasari Suryadi; Rosidah Rosidah; Gunawan Setiadharma (BERITA BIOLOGI, 2010)
The research with objective to understand optimization frequency of supplemented ascorbic acid (microencapsulated vitamin C CFC-90) feeding to control the Koi Herpes Virus (KHV) disease infecting common carp has been done in Fish Disease Laboratory Fishes were reared in plastic container (80 litres), with density of 20 fish sized 10 gram in average. The treatments were: (A) daily application, (B) three daily application, (C) five daily application, and (D) without vitamin C as a control. Examined fishes were challenged to KHV infection after the 21 days rearing period by cohabitation method for 2 weeks. Observations been done on behaviour, clinical signs and mortality of fishes. The results showed that the highest survival rate was found on the application o vitamin C given every 3 days (50.0%); followed by every day (12.5%), every 5 days (7.5%), and the lowest was found on contro group (1.3%). Control techniques in the case of KHV carp populations through the provision of vitamin C immunostimulatory conducted regularly since well before the existence of KHV infection provides the best protective level.